Improving The Quality Of Human Resource In English Dormitories Of Pesantren Sunan Drajat Through Upgrading Program - Shohiyah shobaha (Mudir : Jurnal Manajemen Pendidikan, 2024)
Pesantren Sunan Drajat is one of Islamic boarding schools that has commitment to afford the excellent educational programs. Many efforts have been done to meet the aim of successful education, such as providing the good facilities and qualified educators. Qualified educators become one of the essential factors that determines the success of education. Many studies have been conducted to prove the tight correlation between students’ accomplishment and the quality of educators. Therefore, English dormitories, which are provided by pesantren Sunan Drajat to facilitate the students who wants to improve their English skill, have strong effort to provide the good qualified English tutors to attain the great students’ achievements. This current study aims to investigate how English dormitories of Sunan Drajat manage the human resource in order to improve the quality of their English tutors through their upgrading programs. Qualitative research methodology through observation, interview and documentation was employed to obtain the whole data about how upgrading programs run. This study resulted that upgrading program is kind of teacher training program which is chosen to improve the quality of human resource in English language dormitories of pesantren Sunan Drajat. That program contains of some useful activities such as training to make innovative and interesting English lesson planning, learning English materials handled by one English expert to upgrade the English skill of tutors, preparing teaching media, microteaching, and teaching evaluation. Overall, the challenges are still found during implementing upgrading program, namely lack of tutors’ awareness and motivation to improve the quality of themselves.